PENERAPAN METODE GOAL DIRECTED DESIGN UNTUK EVALUASI DAN PERBAIKAN USER INTERFACE DALAM MENINGKATKAN USER EXPERIENCE PADA APLIKASI HESTIBELL - Meisya Jala Girinda; Tan Amelia; Endra Rahmawati (Jurnal Sistem Informasi Universitas Dinamika, 2022)
Hestibell is a community for everyone to feel valued. The majority of Hestibellits members are women, but men can also join. Hestibell has an application called “Hestibell” which is a platform to support the positive and fun activities held by Hestibell in building a healthy community that can unite members Hestibell with the application, Hestibell can make it easy for members to interact with the features of the Hestibell application to get information on the schedule of activities held every day, get many friends in the community from various cities, make payments when participating in activities, information on loyalty merchandise, cooperate with other parties and information about the community. After conducting interviews with the founders and members of Hestibell, the results showed that the Hestibell application had never been evaluated for the user interface, the appearance of the application was old school, unattractive, the flow of the application was not clear, the application could not develop and compete with other applications. The results of the initial evaluation calculation of the Hestibell application have a mean not reaching 1 so it is included in the